The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/odi.12474
|View full text |Cite
|
Sign up to set email alerts
|

Statin intake is associated with MMP‐1 level in gingival crevicular fluid of patients with periodontitis

Abstract: BACKGROUND This study was conducted to assess if statin intake is associated with clinical parameters of periodontitis and matrix metalloproteinase (MMP) levels in gingival crevicular fluid (GCF) of nondiabetic and diabetic patients. METHODS We first determined the effect of simvastatin on MMP expression in mononuclear cells. We then recruited 117 nondiabetic and diabetic patients, who all had periodontitis and took or did not take statin, and measured periodontal probing depth (PPD) and clinical attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 47 publications
(48 reference statements)
5
27
0
Order By: Relevance
“…30,31 The use of EDTA gel at neutral pH (24%) as a root surface conditioner was carried out for smear layer removal, exposing dentine collagen fibers and increasing the diameter of the dentinal tubules 32,33 which could enhance migration and attachment of fibroblast 34,35 and could allow more SMV local adsorption to the root surface improving its availability. [36][37][38] Many studies reported that EDTA root surface etching could enhance drug availability over the root surfaces or in the GCF like chlorhexidine 39 and doxycycline. 40,41 Filter paper was used for GCF sampling as it is the easiest and a more precise method for GCF collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 The use of EDTA gel at neutral pH (24%) as a root surface conditioner was carried out for smear layer removal, exposing dentine collagen fibers and increasing the diameter of the dentinal tubules 32,33 which could enhance migration and attachment of fibroblast 34,35 and could allow more SMV local adsorption to the root surface improving its availability. [36][37][38] Many studies reported that EDTA root surface etching could enhance drug availability over the root surfaces or in the GCF like chlorhexidine 39 and doxycycline. 40,41 Filter paper was used for GCF sampling as it is the easiest and a more precise method for GCF collection.…”
Section: Discussionmentioning
confidence: 99%
“…4 These could be attributed to the added values of SMV used in the present study for both groups with its known effect on fibroblastic proliferation. 30 SMV was found to inhibit tissue degrading enzymes like MMPs 38,39 and have anti-microbial properties. 40,41 Many studies reported positive results during the regeneration of periodontal bone defects after the application of SMV with methylcellulose gel.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, statins are shown to be effective against A. actinomycetemcomitans and Porphyromonas gingivalis , 2 of the major species of bacteria implicated in periodontitis pathogenesis. Furthermore, statins are shown to inhibit tissue‐degrading enzymes (i.e., matrix metalloproteinases) and to exert a pro‐proliferative effect on mesenchymal stromal cells and endothelial progenitor cells . Statins are also shown to enhance osteoblastic differentiation and viability, bone morphogenetic protein and vascular endothelial growth factor expression and to interfere with bone resorption and osteoclastogenesis …”
Section: Discussionmentioning
confidence: 99%
“…The increased knowledge on the inflammatory pathways involved in periodontitis has prompted the investigation of the effects of anti-inflammatory drugs as strategies to reduce gingival inflammation 16. Recent studies have suggested that cholesterol-lowering drugs such as simvastatin are protective against experimental2,4,17 and human periodontitis 18,19. These evidences have suggested that simvastatin is able to reduce bone loss and modulate the expression/release of inflammatory markers in gingival crevicular fluid samples.…”
Section: Discussionmentioning
confidence: 99%